Proceso de atención de enfermería en paciente de 60 años de edad con infarto agudo de miocardio. - Monar Padilla, Stefania Daniela (2020)
Acute myocardial infarction refers to myocardial necrosis that occurs due to the acute obstruction of a coronary artery. The main symptoms are: chest pain, with irrigation to the neck and jaw, and the left arm. There is also the presence of dyspnea, diaphoresis, nausea and vomiting. The diagnosis is mainly based on the electrocardiogram and the finding of cardiac biomarkers. Initial treatment consists of the use of anticoagulants, beta-blockers, antiplatelet agents, statins, and reperfusion therapy. The present case study was carried out in order to demonstrate how the correct action of the nursing staff influences before a 60-year-old patient with acute myocardial infarction, starting with the cephalocaudal evaluation and the functional patterns of Marjory Gordon, with the aim to describe the patient's condition and evaluate each proposed intervention such as: cardiac care, pain management, and anxiety level. Resulting in the favorable evolution of the patient.